INTEGRATION BETWEEN THE SCIENCE OF MATHEMATICS AND THE SCIENCE OF MATHEMATICS TEACHING METHODS - Toshpulatova Ma'mura Ismoilovna (Scholar Express Journal, 2023)
This article discusses the integration between the science of mathematics and the science of methods of teaching mathematics in order to improve the quality of higher mathematical education in the context of its humanization; the authors propose to integrate mathematical and methodological training.
Keywords: Elementary mathematics; methodical training; methodical orientation of teaching; methodical skills